The role of miRNAs in the diagnosis and treatment of male infertility: a review study - Roya Sinaei; Khosro Jamebozorgi; Hossein Mirshekarpour; Hossein Poormasoumi; Amirhossein Mahdizadeh; Zahra Akbari; Eskandar Taghizadeh (Egyptian Journal of Medical Human Genetics, 2023)
Abstract Infertility is a widespread issue that affects over five million couples globally. The cause of this condition can be related to women, men, or both. Male infertility, as a clinical disorder, can be caused by problems in spermatogenesis, testicular development, epididymal, and sperm maturation. Various methods have been proposed to diagnose and treat this disorder, but in some cases, it still remains idiopathic. Nowadays, the investigation of miRNAs is being discussed for the diagnosis and treatment of male infertility. miRNAs are small non-coding RNAs that regulate the expression of many genes after transcription. The aim of this review is to study miRNAs as noninvasive biomarkers for the diagnosis of infertility, as well as proposed treatment strategies and the challenges ahead in these avenues.